Judgment and Afterlife in Ancient Egypt: The Principle of Ma’at, Osirian Tradition, and the Comparative Context of Eternal Punishment - Jock, Agai Matthew; Kingsley, Kinya Nelson (Journal of Contemporary Rituals and Traditions, 2025)
Purpose: This study investigates the concept of judgment and afterlife in Ancient Egypt with particular attention to the principle of Ma’at and the Osirian tradition, while situating its findings within the comparative context of the doctrine of eternal punishment. The research aims to determine whether the Egyptian system of judgment included the notion of everlasting torment or instead emphasized cosmic balance and annihilation of the unworthy soul. Methodology: Employing a qualitative, interpretive, and historical-comparative approach, the study analyzes primary sources such as the Book of the Dead, funerary inscriptions, and mummification rituals, alongside secondary scholarship in Egyptology and comparative religion. Findings: The findings demonstrate that the Egyptian system of judgment was rooted in the weighing of the heart against the feather of Ma’at, the practice of negative confession, and the tribunal presided over by Osiris and forty-two judges. Punishment was most often conceived as annihilation rather than eternal suffering, and the afterlife was envisioned as a regenerative cosmology tied to the Nile’s agrarian cycles. These results distinguish the Egyptian view fundamentally from the Christian doctrine of hell. The study further highlights the dual function of judgment: as a religious mechanism to ensure cosmic harmony and as a socio-political instrument reinforcing royal legitimacy and social hierarchy. Implications: The implications of this research extend to comparative religious studies, curricular development, and interfaith dialogue, demonstrating that doctrines of eternal hell are historically contingent constructions rather than universal inheritances. Originality and Value: The originality of this study lies in its reinterpretation of Ancient Egyptian eschatology as an autonomous system, independent from post-biblical theological frameworks, thereby offering a new comparative lens to clarify the origins of eschatological doctrines across traditions.